Efecto del manejo agronómico del riego sobre el desarrollo agro productivo del cultivo de maíz bajo las condiciones climáticas del Valle Carrizal- Chone - Cajape Bravo, Lilibeth Cristina (2024)
This study aimed to evaluate the potential impact of agronomic irrigation management on maize cultivation in the Carrizal Valley – Chone through a review of previously conducted works. The methodological approach focused on the literature review related to specific irrigation methodologies, such as Traditional Irrigation (without water deficit) and deficit irrigation methodologies like Deficit Irrigation Control (DIC) and Partial Root Drying (PRD), with the objective of understanding their influence on crop productivity and gross margin in maize cultivation. The literature review highlighted that, as expected, when the crop did not experience water stress, the yield reached its potential, with an average of approximately 30% higher compared to deficit treatments. Regarding deficit methodologies, DIC proved to be the methodology that enhances water productivity compared to others by distributing water based on the crop´s water sensitivity stages. Concerning the PRD methodology, alternating the wetting side every week showed better results on agro- productive variables than alternating every two weeks. Although the results are contingent on the specific conditions of the Carrizal Valley - Chone, the research indicates that adjusting water management is crucial for the sustainability and profitability of maize cultivation in the region. Therefore, this bibliographic analysis emphasizes the imperative need for future field research to validate and quantify these findings, thus providing a solid foundation for decision-making in local agriculture.